2017
DOI: 10.1002/ece3.3316
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and season affect crayfish detection and density inference using environmental DNA

Abstract: Although the presence/absence of aquatic invertebrates using environmental DNA (eDNA) has been established for several species, inferring population densities has remained problematic. The invasive American signal crayfish, Pacifastacus leniusculus (Dana), is the leading cause of decline in the UK's only native crayfish species, Austropotamobius pallipes (Lereboullet). Methods to detect species at low abundances offer the opportunity for the early detection, and potential eradication, of P. leniusculus before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 67 publications
(90 reference statements)
6
71
4
Order By: Relevance
“…However, substantial variation exists in design, validation, and application of species-specific assays, even for the same target species, e.g. invasive signal crayfish P. leniusculus (Agersnap et al, 2017;Dunn et al, 2017;Larson et al, 2017;Harper et al 2018a;Mauvisseau et al, 2018;Robinson et al, 2018). False positives and negatives remain pertinent issues in eDNA monitoring and intuitive counter-strategies are required for their mitigation.…”
Section: Rare and Invasive Species Monitoringmentioning
confidence: 99%
“…However, substantial variation exists in design, validation, and application of species-specific assays, even for the same target species, e.g. invasive signal crayfish P. leniusculus (Agersnap et al, 2017;Dunn et al, 2017;Larson et al, 2017;Harper et al 2018a;Mauvisseau et al, 2018;Robinson et al, 2018). False positives and negatives remain pertinent issues in eDNA monitoring and intuitive counter-strategies are required for their mitigation.…”
Section: Rare and Invasive Species Monitoringmentioning
confidence: 99%
“…eDNA analysis allows early detection even when target species are not directly observed. A few studies have estimated the transport distance of eDNA from the source to about 10 km, depending on population size [64,65], and the permanence of genetic material within the environment at about 10 days, indicating that DNA traces are near contemporary with presence of the species [66,67]. Compared to traditional survey methods (e.g., trapping and visual surveys), eDNA seems to have higher start-up costs for developing and testing the whole assay (eDNA extraction, PCR condition, primers tests, amplicon sequencing), but a few studies suggest that eDNA can reduce total survey costs [68,69].…”
Section: Ednamentioning
confidence: 99%
“…Accurate abundance estimation through eDNA is still challenging and depends on multiple factors such as the number of DNA copies released into the water from an individual, the transport rate of the stream and the stability of eDNA over time [65,78]. Moreover, behaviour and season affect crayfish detection and abundance inference using eDNA, as, for example, it has been shown that ovigerous females release higher DNA levels than males do [67]. Therefore, before the application of quantitative eDNA methods, researchers need to quantify the errors generated in order to estimate abundance, depending on many factors, linked both to the target species and to the specific environment studied (i.e., lotic, lentic and ocean waters).…”
Section: Ednamentioning
confidence: 99%
“…Biological differences include organism size, seasonal presence and senescence, preservation and dispersal strategy, among others. Larger taxa, taxa that are present year‐round or taxa whose DNA is readily transported across long distances by wind or water, may be more likely to be observed in environmental samples than smaller, seasonal and sedentary taxa (Andersen et al., ; Barnes & Turner, ; Buxton, Groombridge, Zakaria, & Griffiths, ; Dunn, Priestley, Herraiz, Arnold, & Savolainen, ; Hemery, Politano, & Henkel, ; Rees et al., ). Even when the same number of cells is present in an environmental sample, the starting copy number of target loci may vary between taxa and tissue type.…”
Section: Introductionmentioning
confidence: 99%